Accountability of Village Fund Management through the Competence of Managers and Internal Control System in Ruteng District, Manggarai Regency, East Nusa Tenggara Province - Lasiyono, Untung; Firdausia, Yuli Kurnia (Archives of Business Research, 2021)
This study is a qualitative research that analyzes the level of accountability for the use of village funds which is studied through the competence aspect of village fund managers and the internal control system of village funds. The subjects were village in rural village fund manager Beo Rahong Village, District of Ruteng, Manggarai Regency, East Nusa Tenggara Province. Meanwhile, the object of research is the competence of managers, internal control systems and accountability of village funds. The data collection technique used a triangulation approach, namely from the source, method and time aspects. While the data analysis used a qualitative descriptive approach by analyzing the results of the data obtained by the triangulation approach. Based on the results of the data and after being analyzed, it shows that the competency aspect of village fund budget managers is still less competent due to the limitations of five things, namely, knowledge, understanding, abilities, values, attitudes and interests . Meanwhile, in terms of aspects of the internal control system that are still not in accordance with the standards as stipulated in Government Regulation Number 60 of 2008 concerning the government’s internal control system, this is due to the manager’s competence not being maximized. Then in terms of accountability for the use of village funds, this has not been realized, this is due to the not yet maximal competence, internal control which is also still not carried out optimally due to limited human resources in mastering information technology and the lack of support for information technology facilities.